Corporate governance a synthesis of theory, research, and practice - Anderson, Ronald; Baker, H. Kent (Harold Kent) 1944- (The Robert W. Kolb series in finance)
"A detailed look at the importance of corporate governance in today's business world. The importance of corporate governance became dramatically clear at the beginning of the twenty-first century as a series of corporate meltdowns from managerial fraud, misconduct, and negligence caused a massive loss of shareholder wealth. As part of the Robert W. Kolb Series in Finance, this book provides a comprehensive view of the shareholder-manager relationship and examines the current state of governance mechanisms in mitigating the principal-agent conflict. This book also offers informed suggestions and predictions about the future direction of corporate governance. Relies on recent research findings to provide guidance through the maze of theories and concepts. Uses a structured approach to put corporate governance in perspective. Addresses essential issues related to corporate governance including the idea of principal-agent conflict, role of the board of directors, executive compensation, corporate monitoring, proxy contests and corporate takeovers, and regulatory intervention"--